Strategic fund development : building profitable relationships that last - Joyaux, Simone P. (Hoboken, N.J. : Wiley, 2011)
'The completely revised and expanded edition of a fundraising classic Strategic Fund Development became an instant classic the day the first edition was released. Now in this expanded third edition, it has been revised cover-to-cover with relevant new information and useful new tools and resources. The book addresses the needs for fundraisers of every level of expertise. Experienced development officers find this an invaluable reference tool for educating their colleagues and boards. New fundraisers get firm grounding in best practice and what it really takes to do this work. Executive directors learn how fundraising fits into the organization and what it takes to make fundraising productive. Contains in-depth analysis about what makes organizations effective, including things like leadership, organizational culture, decision-making processes, systems thinking, and well-managed change. Offers comprehensive strategic planning insights, with detailed steps, sample research tools, retreat agendas, and complete plans. Includes the same tools and resources for fundraising planning. This updated classic provides essential insights, with an extra bonus: purchasers get exclusive access to a website of tools and resources'--
Includes bibliographical references and index.
Keywords: Fund raising